The Learning Needs Interview - Murray, Hugh; Fenman (Cambridgeshire Fenman, 2000)
The Learning Needs Interview is the first part of the Fenman series dealing with Managing Learning at Work. In this part, we meet the characters in the series and follow them through the process of identifying learning needs ahead of putting together a plan to meet those needs. Although the Learning Needs Interview is the first part of this trilogy it is completely stand-alone programme and does not need to be used as part of series of training sessions using all three videos
User's Guide
Keywords: Learning Needs